Synchronization of Calcifying Odontogenic Cyst and Aneurysmal Bone Cyst: A Case Report - Jahanshah Salehinejad; Baratollah Shaban; Tahere Mehri; Azam Roshanmir (Mashhad University of Medical Sciences, 2017)
Although aneurysmal bone cysts and calcifying odontogenic cysts accompanied with other lesions are reported in the literature, the simultaneous occurrence of these two distinct lesions has not been reported. To the best of our knowledge, this is the first report describing co-occurrence of these two lesions located in the left mandibular ramusin a 36-year-old woman.